Isfahan is half the world : memories of a Persian boyhood - Jamālzādah, Muḥammad ʻAlī (Princeton library of Asian translations., 1983)
Mohammad Ali Jamalzadeh, acclaimed as the father of modern Persian short story, wrote this work. Sar o Tah-e Yak Karbas. to provide his fellow Iranians a memoir in story form of traditional Islamic life in Iran before westernization. Originally published in 1983. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.